2014
DOI: 10.1167/14.9.16
|View full text |Cite
|
Sign up to set email alerts
|

Distinguishing bias from sensitivity effects in multialternative detection tasks

Abstract: Studies investigating the neural bases of cognitive phenomena increasingly employ multialternative detection tasks that seek to measure the ability to detect a target stimulus or changes in some target feature (e.g., orientation or direction of motion) that could occur at one of many locations. In such tasks, it is essential to distinguish the behavioral and neural correlates of enhanced perceptual sensitivity from those of increased bias for a particular location or choice (choice bias). However, making such … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
106
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(112 citation statements)
references
References 41 publications
4
106
0
Order By: Relevance
“…Luo and Maunsell (23) adopted a classic signal detection framework (24) and showed that attention-related modulation in visual cortical area V4 was related to changes in perceptual sensitivity, but not to changes in selection criterion; in their discussion, they suggest the complementary possibility that criterion shifts are mediated by subcortical structures such as the SC. This suggestion is consistent with other physiological results implicating the SC in criterion changes (25) and stimulus selection (26), and with recent models of attention that draw distinctions between changes in perceptual sensitivity and changes in choice bias (27). If the SC were associated with criterion shifts and not perceptual sensitivity, then when activity in the SC is suppressed by reversible inactivation animals should still show changes in perceptual sensitivity, because this aspect of their behavior would be mediated by cortical circuits left intact during the SC inactivation.…”
supporting
confidence: 92%
See 3 more Smart Citations
“…Luo and Maunsell (23) adopted a classic signal detection framework (24) and showed that attention-related modulation in visual cortical area V4 was related to changes in perceptual sensitivity, but not to changes in selection criterion; in their discussion, they suggest the complementary possibility that criterion shifts are mediated by subcortical structures such as the SC. This suggestion is consistent with other physiological results implicating the SC in criterion changes (25) and stimulus selection (26), and with recent models of attention that draw distinctions between changes in perceptual sensitivity and changes in choice bias (27). If the SC were associated with criterion shifts and not perceptual sensitivity, then when activity in the SC is suppressed by reversible inactivation animals should still show changes in perceptual sensitivity, because this aspect of their behavior would be mediated by cortical circuits left intact during the SC inactivation.…”
supporting
confidence: 92%
“…SDT-based models are often used to describe both detection and two-alternative forced-choice tasks (24). Extensions of this framework to multiple alternatives have been described in detail previously (27,35). Our model is derived in a manner similar to that of Sridharan et al (27) and we therefore superficially recapitulate its derivation.…”
Section: Methodsmentioning
confidence: 93%
See 2 more Smart Citations
“…We will 30 first address the attention-driven changes in visual processing and 31 how they could benefit behavior (Section 1), then turn to some 32 methodological concerns regarding measuring attention at a 33 behavioral level (Section 2), review the evidence for several areas 34 as sources of attentional modulation (Section 3), and finally 35 examine experiments seeking to link attention in these source 36 areas to the signatures previously discussed (Section 4). (Mitchell et al, 2007;Cohen and Maunsell, 2009), 69 enhanced contrast sensitivity (Reynolds et al, 2000), increased 70 synaptic efficacy (Briggs et al, 2013), changes in noise correlations 71 between neurons (Mitchell et al, 2009;Ruff and Cohen, 2014; 72 Cohen and Maunsell, 2009), decreases in low-frequency LFP power 73 and coherence (Fries et al, 2001(Fries et al, , 2008Mitchell et al, 2009), 74 increases in gamma-band LFP power (Fries et An enhanced neuronal representation of the target stimulus 86 could underlie the behavioral benefits of attention, including 87 greater sensitivity (Sridharan et al, 2014), greater spatial resolu-88 tion (Carrasco, 2011), and faster response times (Posner, 1980). 89 Here we summarize the potential representational benefits of the 90 reported signatures of attention.…”
mentioning
confidence: 99%